Biology and Survival of Pseudomonas Solanacearum in Malaysia - Abdullah, Hiryati (1988)
Bacterial wilt, caused by Psetrlaronas solanacearum (Smith, 1896) Smith 1914, is an important disease of many crop plants. The lack of a truly effective method of control for the disease, especially in the tropics, has been attributed to the many strains of the pathogen and the lack of information on the ecology am the variation in the pathogen population. The present study was therefore conducted to elucidate some aspects of the ecology am variation of the pathogen in Malaysia which would be useful in understanding the pathogen for the formulation of more effective control measures.